Novel transcriptome networks are associated with adaptation of capsicum fruit development to a light-blocking glasshouse film - He, Xin; Solis, Celymar A.; Chavan, Sachin G.; Maier, Chelsea; Wang, Yuanyuan; Liang, Weiguang; Klause, Norbert; Ghannoum, Oula; Cazzonelli, Christopher I.; Tissue, David T.; Chen, Zhong-Hua (Frontiers in Plant Science, 2023)
Light-blocking films (LBFs) can contribute to significant energy savings for protected cropping via altering light transmitting, such as UVA, photosynthetically active radiation, blue and red spectra affecting photosynthesis, and capsicum yield. Here, we investigated the effects of LBF on orange color capsicum (O06614, Capsicum annuum L.) fruit transcriptome at 35 (mature green) and 65 (mature ripe) days after pollination (DAP) relative to untreated control in a high-technology glasshouse. The results of targeted metabolites showed that LBF significantly promotes the percentage of lutein but decreased the percentage of zeaxanthin and neoxanthin only at 35 DAP. At 35 DAP, fruits were less impacted by LBF treatment (versus control) with a total of 1,192 differentially expressed genes (DEGs) compared with that at 65 DAP with 2,654 DEGs. Response to stress and response to light stimulus in biological process of Gene Ontology were found in 65-DAP fruits under LBF vs. control, and clustering analysis revealed a predominant role of light receptors and phytohormone signaling transduction as well as starch and sucrose metabolism in LBF adaptation. The light-signaling DEGs, UV light receptor UVR8, transcription factors phytochrome-interacting factor 4 (PIF4), and an E3 ubiquitin ligase (COP1) were significantly downregulated at 65 DAP. Moreover, key DEGs in starch and sucrose metabolism (SUS, SUC, and INV), carotenoid synthesis (PSY2 and BCH1), ascorbic acid biosynthesis (VTC2, AAO, and GME), abscisic acid (ABA) signaling (NCED3, ABA2, AO4, and PYL2/4), and phenylpropanoid biosynthesis (PAL and DFR) are important for the adaptation of 65-DAP fruits to LBF. Our results provide new candidate genes for improving quality traits of low-light adaptation of capsicum in protected cropping.